Emotional intelligence and stress coping strategies among undergraduates in Kota Samarahan - Carina, anak Nicholas Neru (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The aim of this study was to investigate the relationship between emotional intelligence and stress coping strategies among undergraduates in Kota Samarahan. Emotional intelligence and stress coping strategies characteristic of the undergraduates in Kota Samarahan were also explained. A 33-items in Schutte’s Self-Reported Inventory developed by Schutte et.al (1998) and a 36-items in Adolescent Coping Scale questionnaires developed by Frydenberg and Lewis (1993) were administrated to 94 undergraduates in Kota Samarahan. Data was tested using Pearson Correlation. The findings showed significant relationship between emotional intelligence and stress coping strategies. The respondents' emotional intelligence were characterized balancely by emotions perception, managing self-relevant emotions, managing others' emotions and utilizing emotions. Most respondent preferred reference to other's coping and productive coping. This study suggests that emotional intelligence is emphasized in youth development program especially in stress coping strategies.